Quinoid to benzenoid transition-driven glutathione sensing: Dual-emission carbon dots and smartphone-based ratiometric fluorescence analysis - Al-Montaser Bellah H. Ali; Ashraf M. Mahmoud; Yousef A. Bin Jardan; Aya M. Mostafa; James Barker; Mohamed M. El-Wekil (Talanta Open)
This study presents a novel and sensitive method for the determination of glutathione (GSH), a crucial antioxidant and cellular protectant, using dual blue/orange-emitting carbon dots (BOCDs) and phenolphthalein (PHP). The sensing system operates at pH 9.0, exploiting the unique optical properties of BOCDs with emission peaks at 420 nm and 570 nm. In alkaline conditions, PHP develops a pink color that selectively quenches the 570 nm emission of the CDs while leaving the 420 nm peak unaffected. Upon introduction of GSH, the quinoid structure of PHP is converted to its benzenoid form via Michael addition, resulting in the disappearance of the pink color and subsequent restoration of the 570 nm fluorescence. This mechanism, utilized for the first time in GSH detection, offers a distinct advantage over previous methods that primarily relied on GSH's complexation capabilities. The analytical capabilities of the BOCDs/PHP ratiometric probe were extensively evaluated through multiple spectroscopic methods to understand its sensing mechanism. Performance analysis revealed impressive analytical figures of merit: the method exhibited strong linearity with a correlation coefficient of 0.9985, provided sensitive detection across a broad concentration range from 0.01 to 8.0 μM, and achieved a remarkably low detection limit of 3.33 nM. The method's versatility was enhanced through the development of a dual-mode smartphone platform, enabling both colorimetric and fluorometric GSH detection. Practical validation using human serum samples demonstrated the method's robustness in complex biological matrices, achieving high recovery rates between 98.5 % and 101.0 %, confirming its suitability for real-world clinical applications. This novel strategy combines the sensitivity of ratiometric fluorescence with the convenience of smartphone-based detection, offering a promising tool for GSH monitoring in clinical and research settings.